Determination of total sennosides and sennosides A, B, and A1 in senna leaflets, pods, and tablets by two-dimensional qNMR - Serhat Sezai Çiçek; Calisto Moreno Cardenas; Ulrich Girreser (Molecules, 2022)
In the present work, a two-dimensional qNMR method for the determination of sennosides was established. Using band-selective HSQC and the cross correlations of the characteristic 10–10’ bonds, we quantified the total amount of the value-determining dianthranoids in five minutes, thus, rendering the method not only fast, but also specific and stability indicating. The validation of the method revealed excellent accuracy (recovery rates of 98.5 to 103%), precision (RSD values of 3.1%), and repeatability (2.2%) and demonstrated the potential of 2D qNMR in the quality control of medicinal plants. In a second method, the use of 2D qNMR for the single analysis of sennosides A, B, and A1 was evaluated with acceptable measurement times (31 min), accuracy (93.8%), and repeatability (5.4% and 5.6%) for the two major purgatives sennoside A and B. However, the precision for sennoside B and A1 was not satisfactory, mainly due to the low resolution of the HSQC signals of the two compounds.
Keywords: aloin; anthranoids; anthrone glycosides; Cassia acutifolia; Cassia angustifolia; laxatives; quality control; quantitative NMR; Senna alexandrina; surrogate standard